003 Towards optimal patient involvement in guideline development groups. (15th August 2013) - Lange-Tichelaar, T De; Pittens, C; Verhoof, E; Maes, L; Kersten, S; Broerse, J
Abstract : Background: The involvement of patient representatives in guideline development groups (GDGs) could increase legitimacy and quality of clinical practice guidelines (CPGs), since the experiential knowledge of patients could complement scientific evidence. By their involvement, patients have the opportunity to share (consultation) and incorporate their views and experiences into CPGs (decision-making). Although the importance of this approach is emphasised, little methodological support and systematic reflection exist on effective strategies. Objectives: To gain insight in how patient involvement in GDGs can be optimised in order to develop strategies which can be implemented in practice. Methods: The evaluation consisted of a desk study and 23 semi-structured interviews with stakeholders in CPGs, including patient representatives. The acquired insights were used to develop an evaluation framework, which guided monitoring and evaluation of four ongoing oncological guideline development processes. Validation took place through a triangulated approach (e.g. observations, document-analyses, interviews). Two patient representatives were included in the research team. Results: The evaluation revealed that successful patient involvement in GDGs depends on a broad scale of factors (e.g. members of the GDGs, support of patient representatives) which could facilitate or constrain patient involvement. The factors were used to develop practical strategies for patient involvement, ranging from preparation meetings to regular reflections with the patient representatives and dialogue sessions with patients. Discussion: The strategies could lead to more successful patient involvement in GDGs and provide valuable insights on how to involve patients in guideline development processes on other disease areas.